EVALUATION OF WOUND HEALING IN POST-SURGICAL PATIENTS CAESAR THOSE USING ANTIBIOTIC DRUGS AT TANJUNG PURA HOSPITAL - Mayang Sari; Sri Handayani; Rizka Hasmi Nasution; Nurmadiah Nurmadiah (Journal of Medical Genetics and Clinical Biology, 2024)
Introduction The World Health Organization (WHO) estimates that 5-15% of births globally are surgical cesarean section. Indonesian Health 2017 shows that 17.02% of deliveries in Indonesia are cesarean sections. Surgical wound infections are infections from wounds obtained after surgery. This infection can occur 30-90 days after surgery. Appropriate use of prophylactic antibiotics intraoperatively can reduce Surgical wound infections. Antibiotics are the most widely used class of drugs related to bacterial infectious diseases. Types of research used is prospective survey research with an approach of studying and testing hypotheses related to ongoing experience. Sample studies were 20 respondents. This research uses quantitative descriptive data analysis with a prospective research design. Research results At the Pharmacy Installation at the Tanjung Pura Regional General Hospital, surgical wounds began to close/dry as much as 70% (14 patients) for compliance with the use of antibiotics according to the right indication, right dose, right patient, right drug. Conclusion of this research is that administering antibiotics affects wound healing in patients and can ensure accuracy in suitability. It is recommended that the hospital review the cleanliness of the surgical area in order to improve the quality of the hospital.